2005
DOI: 10.1121/1.2010288
|View full text |Cite
|
Sign up to set email alerts
|

Finding intonational boundaries using acoustic cues related to the voice source

Abstract: Acoustic cues related to the voice source, including harmonic structure and spectral tilt, were examined for relevance to prosodic boundary detection. The measurements considered here comprise five categories: duration, pitch, harmonic structure, spectral tilt, and amplitude. Distributions of the measurements and statistical analysis show that the measurements may be used to differentiate between prosodic categories. Detection experiments on the Boston University Radio Speech Corpus show equal error detection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(34 citation statements)
references
References 8 publications
0
32
1
1
Order By: Relevance
“…Tone language (Chinese) listeners who have extensive experience with the linguistic use of pitch in their native language showed stronger, more asymmetric processing of contour and interval cues than non-tone language listeners (English) who lack extensive pitch expertise. That is, pitch is less important for English prosodic perception relative to amplitude and duration cues (Choi et al, 2005;Kochanski et al, 2005). Previous studies have shown enhanced cortical responses to isolated linguistic pitch patterns (Gandour et al, 2000;Chandrasekaran et al, 2009a,b;Bidelman and Lee, 2015).…”
Section: Discussionmentioning
confidence: 95%
“…Tone language (Chinese) listeners who have extensive experience with the linguistic use of pitch in their native language showed stronger, more asymmetric processing of contour and interval cues than non-tone language listeners (English) who lack extensive pitch expertise. That is, pitch is less important for English prosodic perception relative to amplitude and duration cues (Choi et al, 2005;Kochanski et al, 2005). Previous studies have shown enhanced cortical responses to isolated linguistic pitch patterns (Gandour et al, 2000;Chandrasekaran et al, 2009a,b;Bidelman and Lee, 2015).…”
Section: Discussionmentioning
confidence: 95%
“…Classical theories (e.g., Fry, 1954) accorded fundamental frequency the key role in stress perception, with duration and intensity (amplitude) playing secondary roles. More recent investigations using natural speech have shown that amplitude and duration cues play a stronger role in prosodic prominence than fundamental frequency (Choi, Hasegawa-Johnson, & Cole, 2005;Greenberg, 1999;Kochanski, Grabe, Coleman, & Rosner, 2005). For example, Greenberg (1999) described an automatic prosodic algorithm developed to label stressed and unstressed syllables in a corpus of spontaneous speech.…”
Section: Introductionmentioning
confidence: 98%
“…At this time, relatively little research on the phonetic effects of (putative) phrasal prosodic prominence has been done (but see van and the gradient likelihood of observing or blocking allophonic phonetic variation across these boundaries, such as fortition/lenition effects, mirror the strength or level of these boundaries (Wightman et al 1992, Dilley et al (1996, Byrd & Saltzman (2003), Féry (2003, Keating (2003), Choi et al (2005), Yoon et al 2007). By contrast, no such homomorphism would be definable between the syntactic or semantic representation of We would simply add here that the phonetic prominence Truckenbrodt observes is arguably a reflex of phonological phrase-level prominence.…”
Section: Implications Of Pitch Findings For the Grammarmentioning
confidence: 99%